Avaliação da atividade antimicrobiana dos compostos fitoquímicos da fração acetato de etila do extrato de folhas de urucum (Bixa orellana) em modelo experimental de bexiga neurogênica - COUTINHO, Gabrielle Guedes (2022)
Neurogenic Bladder (BN) or lower urinary tract neurogenic dysfunction is a medical and social problem resulting from abnormal neural communication between the bladder and the nervous system. It is common for patients with BN to have recurrent urinary tract infections. This dysfunction has clinical and physical relevance in the quality of life of patients affected by it. Based on the importance of treating bacterial infections that affect patients with BN, it becomes necessary to search for new therapeutic alternatives, and antimicrobials originating from plants are presented as a favorable therapeutic practice. The objective of this research was to perform in vitro and in vivo analyzes of the Ethyl Acetate fraction from Bixa Orellana leaves (BoEA), and the compound isolated from the fraction, ellagic acid against microorganisms that cause neurogenic cystitis in an experimental model of neurogenic bladder in rats, through the experimental surgical protocol by complete spinal cord transection. The in vitro results showed that BoEA had a Minimum Inhibitory and Bactericidal Concentration of 6.25 mg/mL, while ellagic acid, MIC and CBM of 25 mg/mL against E. coli isolated in the experimental model. In in vivo assays, the BoEA group (50mg/kg) showed no statistical difference in hematological parameters when compared to the negative control group. The association group (ellagic acid with antibiotic) showed greater efficacy among the proposed treatments. As for urinalysis, the groups treated with ellagic acid and with the association had substantial improvement in these parameters. In the CFU assay, it can be seen that all the proposed treatments were able to reduce the number of colonies, proving the therapeutic efficacy of ellagic acid and its association with antibiotics for the treatment of E.coli infections. This work can contribute to the process of searching for therapeutic alternatives with the use of medicinal plants, mainly with the use of B. orellana and its photochemical compounds for the treatment of urinary infections resulting from neurogenic bladder.